Q4. Show that the following four conditions are equivalent :
(i) A B(ii) A – B =
(iii) A
B = B (iv) A
B = A
First, we need to show A B
A – B =
Let A B
To prove : A – B =
Suppose A – B
this means, x A and x
B , which is not possible as A
B .
SO, A – B = .
Hence, A B
A – B =
.
Now, let A – B =
To prove : A B
Suppose, x A
A – B = so x
B
Since, x A and x
B and A – B =
so A
B
Hence, A B
A – B =
.
Let A B
To prove : A B = B
We can say B A
B
Suppose, x A
B
means x A or x
B
If x A
since A B so x
B
Hence, A B = B
and If x B then also A
B = B.
Now, let A B = B
To prove : A B
Suppose : x A
A A
B so x
A
B
A B = B so x
B
Hence,A B
ALSO, A B
A
B = B
NOW, we need to show A B
A
B = A
Let A B
To prove : A B = A
Suppose : x A
We know A B
A
x A
B Also ,A
A
B
Hence, A B = A
Let A B = A
To prove : A B
Suppose : x A
x A
B ( replacing A by A
B )
x A and x
B
A
B
A B
A
B = A